Bio-inspired toe-like structure for low-frequency vibration isolation. (1st January 2022) - Yan, Ge; Zou, Hong-Xiang; Wang, Sen; Zhao, Lin-Chuan; Wu, Zhi-Yuan; Zhang, Wen-Ming
Highlights: A toe-like structure (TLS) is proposed for low-frequency vibration isolation. The structure is obtained by imitating toe with nonlinear stiffness and damping. Adjustable low resonant frequency and beneficial damping effect can be obtained. It provides a feasible way for passive vibration isolation in low frequency band. Abstract: Inspired by the cushioning effect of the felid paws in contact with the ground, a novel bio-inspired toe-like structure (TLS) is developed and systematically studied for low-frequency vibration isolation. The TLS consists of two rods with different length (as phalanxes) and a linear spring (as muscle). Based on Hamiltonian principle, the dynamic model is established considering spring deformation and joint rotation damping. The derived equivalent stiffness reveals that the proposed TLS possesses favorable high static and low dynamic stiffness (HSLDS) characteristics in a wide displacement range. Besides, displacement transmissibility suggests that the proposed TLS isolator has low resonance frequency and can effectively isolate base excitation at low frequencies. Comprehensive parameter analysis shows that the inherent nonlinearities in stiffness and damping is conductive to vibration isolation and can be designed/adjusted on demand by selecting suitable structural parameters. This flexibility gives TLS advantages and great potential in extensive engineering applications when subjected to variable vibration loads. A prototype is fabricated and tested for a comprehensive recognize of its advantageous vibration isolation performance in low frequency band. The vibration with excitation frequency higher than 3 Hz can be effectively isolated. This novel bio-inspired TLS provides a feasible approach to passive vibration control and isolation in low frequency band.